The Usage of Human IGHJ Genes Follows a Particular Non-random Selection: The Recombination Signal Sequence May Affect the Usage of Human IGHJ Genes - Shi, Bin; Dong, Xiaoheng; Ma, Qingqing; Sun, Suhong; Ma, Long; Yu, Jiang; Wang, Xiaomei; Pan, Juan; He, Xiaoyan; Su, Danhua; Yao, Xinsheng (Frontiers in Genetics, 2020)
The formation of the B cell receptor (BCR) heavy chain variable region is derived from the germline V(D)J gene rearrangement according to the “12/23” rule and the “beyond 12/23” rule. The usage frequency of each V(D)J gene in the peripheral BCR repertoires is related to the initial recombination, self-tolerance selection, and the clonal proliferative response. However, their specific differences and possible mechanisms are still unknown. We analyzed in-frame and out-of-frame BCR-H repertoires from human samples with normal physiological and various pathological conditions by high-throughput sequencing. Our results showed that IGHJ gene frequency follows a similar pattern which is previously known, where IGHJ4 is used at high frequency (>40%), IGHJ6/IGHJ3/IGHJ5 is used at medium frequencies (10%~20%), and IGH2/IGHJ1 is used at low frequency (<4%) under whether normal physiological or various pathological conditions. However, our analysis of the recombination signal sequences suggested that the conserved nonamer and heptamer and certain 23 bp spacer length may affect the initial IGHD-IGHJ recombination, which results in different frequencies of IGHJ genes among the initial BCR-H repertoire. Based on this "initial repertoire", we recommend that re-evaluation and further investigation are needed when analyzing the significance and mechanism of IGHJ gene frequency in self-tolerance selection and the clonal proliferative response.